Lecture d’albums de littérature à l’école élémentaire - Sandra Dobek (Strenae)
In primary school, apprentice reader pupils acquire decoding, lexical and narrative skills which enable them to progressively become expert readers. They are thus able to use comprehension strategies that enable them to gain access to the meaning of the books they read. Literary picture books for children contribute to develop these skills. However, their mixed features, bringing images and texts together, may sometimes turn out to be an obstacle to their use in class. After an analysis of the place of picture books in the curriculum of the « Éducation nationale », this testimony centers around classroom practice and field considerations. It finally ponders on the use of this medium in cycle 3.